The adipokine apelin-13 induces expression of prothrombotic tissue factor - Cirillo, Plinio; Ziviello, Francesca; Pellegrino, Grazia; Conte, Stefano; Cimmino, Giovanni; Giaquinto, Alessandro; Pacifico, Francesco; Leonardi, Antonio; Golino, Paolo; Trimarco, Bruno (Thrombosis and Haemostasis, 2015)
Adipocytes are cells able to produce and secrete several active substances (adipokines) with direct effects on vascular cells. Apelin, one of the most recently identified adipokines has been studied in cardiovascular system physiology in regard to vessel vasodilation and myocardial contraction, but it has not yet completely characterised for its pathophysiological role in cardiovascular disease and especially in acute coronary syndromes (ACS). Several studies have indicated that tissue factor (TF) plays a pivotal role in the pathophysiology of ACS by triggering the formation of intracoronary thrombi following endothelial injury. This study investigates the effects of apelin 12 and apelin 13 on TF in human umbilical endothelial cells (HUVECs) and monocytes. Cells were stimulated with increasing concentrations of apelin 12 or apelin 13 and then processed to evaluate TF-mRNA levels by real-time PCR as well as TF expression/activity by FACS analysis and pro-coagulant activity. Finally, a potential molecular pathway involved in modulating this phenomenon was investigated. We demonstrate that apelin 13 but not apelin 12 induces transcription of mRNA for TF. In addition, we show that this adipokine promotes surface expression of TF that is functionally active. Apelin 13 effects on TF appear modulated by the activation of the G-protein-transcription factor nuclear factor (NF)-ΚB axis since G-protein inhibitors suppressed NF-ΚB mediated TF expression. Data of the present study, although in vitro, indicate that apelin-13, induces a procoagulant phenotype in HUVECs and monocytes by promoting TF expression. These observations support the hypothesis that this adipokine might play a relevant role as an active partaker in athero-thrombotic disease.
Keywords: Adipokines; atherothrombosis; tissue factor